THE CORRELATION BETWEEN BULLYING BEHAVIOR AND THE RISK OF POST-TRAUMATIC STRESS DISORDER AMONG ADOLESCENTS AT MTS AHMAD YANI JABUNG - Fadhilla Putri Hardiyanto; Risna Yekti Mumpuni; Kurnia Laksana (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Bullying is a traumatic experience that can result in various developmental problems in adolescents, particularly those related to mental health. Some individuals may develop post-traumatic stress disorder (PTSD) as a result of experiencing traumatic life events. Objectives: This study aims to investigate the impact of bullying on PTSD among adolescents at MTs Ahmad Yani Jabung Methods: This study used a quantitative, cross-sectional, correlational research design. A proportional stratified random sampling technique was used, involving 97 students as participants. The bullying behavior, as the independent variable, was measured using a Likert-scale questionnaire developed by Chrysanthou and Chrysolavantis (2018). The dependent variable, risk of PTSD, was assessed using the PTSD Reaction Index questionnaire. The Spearman rank correlation test was used for data analysis. Results: The correlation coefficient value (r = 0.309) and the p-value (p = 0.002, where p < 0.05) indicated a significant correlation between bullying behavior and the likelihood of PTSD among adolescents at MTs Ahmad Yani Jabung. Furthermore, bullying behavior was found to be positively and significantly correlated with the risk of PTSD in adolescents. Conclusions: Since the majority of respondents were at risk of developing PTSD and nearly half of all respondents had experienced moderate levels of bullying, it can be concluded that bullying behavior is associated with the risk of PTSD among adolescents at MTs Ahmad Yani Jabung.